What semantic dementia teaches us about the functional organization of the left posterior fusiform gyrus. (November 2017) - Merck, Catherine; Corouge, Isabelle; Jonin, Pierre-Yves; Desgranges, Béatrice; Gauvrit, Jean-Yves; Belliard, Serge
Abstract: After demonstrating the relative preservation of fruit and vegetable knowledge in patients with semantic dementia (SD), we sought to identify the neural substrate of this unusual category effect. Nineteen patients with SD performed a semantic sorting task and underwent a morphometric 3T MRI scan. The grey-matter volumes of five regions within the temporal lobe were bilaterally computed, as well as those of two recently described areas (FG1 and FG2) within the posterior fusiform gyrus. In contrast to the other semantic categories we tested, fruit and vegetable scores were only predicted by left FG1 volume. We therefore found a specific relationship between the volume of a subregion within the left posterior fusiform gyrus and performance on fruits and vegetables in SD. We argue that the left FG1 is a convergence zone for the features that might be critical to successfully sort fruits and vegetables. We also discuss evidence for a functional specialization of the fusiform gyrus along two axes (lateral medial and longitudinal), depending on the nature of the concepts and on the level of processing complexity required by the ongoing task. Highlights: We studied the neural substrate of fruit & vegetable knowledge in semantic dementia. This knowledge is linked to left FG1 volume (subregion of posterior fusiform gyrus). The left FG1 might be a convergence zone for the features of fruits and vegetables. We provide evidence for the functional specialization of the fusiform gyrus.